Effect of lung T lymphocytes on fibroblasts in idiopathic pulmonary fibrosis and extrinsic allergic alveolitis. Issue 6 (June 1990) - Selman, M; Gonzalez, G; Bravo, M; Sullivan-Lopez, J; Ramos, C; Montano, M; Barquin, N; Vadillo, F
Abstract : Increased fibroblast replication and interstitial collagen accumulation occur commonly in the interstitial lung disease that progress to fibrosis. The processes controlling lung fibrogenesis are not completely understood, however. This study was designed to analyse the influence of T lymphocytes from lung tissue obtained at open lung biopsy from four patients with idiopathic pulmonary fibrosis and four patients with extrinsic allergic alveolitis on fibroblast proliferation and collagen synthesis in vitro. Lung T cell supernatants from patients with both diseases induced a moderate but significant inhibition of human lung fibroblast cell line growth. In contrast, there was a clear difference in the effect of T cells from the two groups of patients in relation to collagen production. Lung T lymphocytes from all four patients with idiopathic pulmonary fibrosis produced a substantial increase in collagen synthesis (from 371% to 514% of control values), whereas T cells from three of the four patients with extrinsic allergic alveolitis induced a significant decrease in collagen production (to 35%, 36%, and 43% of control values); in the fourth case there was an increase in collagen synthesis but this was lower than that seen with T cells from any of the patients with idiopathic pulmonary fibrosis. Peripheral T cells from six patients and control subjects caused a small increase in fibroblast proliferation and no change in collagen synthesis. The findings suggest that at least two types of interaction occur between lung T cells and fibroblasts in these disorders. A variable degree of inhibition of cell proliferation is observed in response to lung T cell supernatants from patients with both idiopathic pulmonary fibrosis and extrinsic allergic alveolitis; a substantial increase in collagen synthesis is triggered by lymphokines from patients with idiopathic pulmonary fibrosis.